Acylation of blueberry anthocyanins with maleic acid: Improvement of the stability and its application potential in intelligent color indicator packing materials. (January 2021) - Fei, Peng; Zeng, Fansen; Zheng, Shiyu; Chen, Qiaoling; Hu, Yonghua; Cai, Jie
Abstract: Aim at improving the poor stability of natural anthocyanins applied in intelligent color indicator packing materials, anthocyanins from blueberry was acylated with maleic anhydride through means of solid-phase grafting method. Fourier Transform Infrared Spectroscopy (FTIR) analysis demonstrated that maleic acid was successfully grafted onto blueberry anthocyanins. All the four acylated anthocyanins (with different acylated degree) were better in stability, but were slightly less efficient at scavenging the DPPH radical, compared with their native non-acylated form. An-MA2 (acylated degree was 7.68%) got the lowest color loss (27.62% at 19th day), 23.19% lower than that of An-MA0 (native anthocyanins). After reacting with maleic anhydride, anthocyanins kept its pH-color response characteristics and showed distinct color differences at different pH value. In addition, the NH3 response characteristics of acylated anthocyanins were similar to those of non-acylated anthocyanins, but lagged slightly in response speed. Graphical abstract: Image 1 Highlights: Maleic acid was grafted on blueberry anthocyanins through solid-phase grafting method. The stability of blueberry anthocyanins were improved after acylation reaction. The grafting of maleic acid retained the pH-color response characteristics of anthocyanins.